EFFICIENT PERSONNEL - Kasim S. Biktyakov (Plekhanov Russian University of Economics, 2017)
The article deals with issues of forming an efficient team, which is an important element of company success. Now it is a group or a united team that becomes a serious factor, when passing over from hierarchy to functional processes management is over. Functional divisions are replaced by teams. During the research the author mentions that forming a team and a group is envisaged by the fact that results of work exceed the sum of results of separate workers. He shows that forming effective teams is a very valuable skill.